Cytoplasmic Her2/neu immunohistochemical staining in breast cancer; From a molecular point of view - Akbar Safaei; Ahmad Monabati; Maral Mokhtari; Mehdi Montazer (Iranian Society of Pathology, 2019)
The most widely used guideline for the breast cancer biomarker assessment and reporting (the 2013 ASCO/CAP guideline) does not state the unusual occurrence of cytoplasmic Her2/neu staining (1, 2). We recently encountered a T2N1Mx ductal adeno-carcinoma which consisted of two dissimilar tumor cell populations. The more prominent population (75% of tumor cells) was made up of sheets of neuroendocrine-like cells (NEL) and the other tumor cell population had a usual adenocarcinomatous histomorphology (UAC) (Fig. 1A). The NEL was ER+ (clone 073), PgR-(clone 636), 40% ki67 with distinct dot-like cytoplasmic Her2 staining (clone CB11) which is considered as negative regarding the current guidelines. The UAC was ER+, PgR+, 20% ki67, and Her2 negative (Fig. 1A-C). Moreover, NEL did not react with either chromogranin or synaptophysin, but it expressed neuron-specific enolase (NSE). Dual color Her2/neu chromogenic in situ hybridization probes (chromogenic ISH) established that both components were not amplified for this oncoprotein gene (Fig. 1D).